ENTANGLED GONZO, VIOLENCE OF REPRESENTATION AND A MOSAIC OF NATIONAL FANTASIES, OR ABOUT THE “UKRAINIAN TRILOGY” BY ZIEMOWIT SZCZEREK. - Kupidura, Ryszard (Porównania, 2019)
Ryszard Kupidura, ENTANGLED GONZO, VIOLENCE OF REPRESENTATION AND A MOSAIC OF NATIONAL FANTASIES, OR ABOUT THE “UKRAINIAN TRILOGY” BY ZIEMOWIT SZCZEREK. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 55-67. ISSN 1733-165X. The aim of this paper is the analysis of three books by Ziemowit Szczerek: Mordor will come and eat us (2013), Tattoo with tryzub (2015) and Intermarium (2017), which due to the presence of topics related to the eastern neighbor of Poland, the author of the article combines in a „Ukrainian trilogy”. The problems addressed in the text include among others: the issue of genre status of Szczerek’s oeuvre; questions about implications of writing about the country with postcolonial status and an attempt to approach the Ukrainian situation from a supra-regional perspective.